From Democratic Erosion to Autocratization: Patterns and Trends in the Twenty-First Century - Camilo Junior, Valter Geronimo (Revista de Derecho, 2025)
Democratic erosion emerges as a complex global phenomenon that demands a critical analysis of its relationship with the rise of autocratic regimes. This article investigates how this democratic decline fosters autocratization, questioning whether immune democracies exist and how institutions can maintain their resilience in the face of crises. Through a qualitative literature review, contemporary patterns are analyzed, such as the backsliding in Hungary and polarization in the United States, which reveal structural vulnerabilities: institutional weakness, socioeconomic inequalities, and the instrumentalization of the political system. The study is organized into four axes: (1) the scope of erosion, demonstrating that even consolidated democracies are not exempt; (2) its historical and economic roots; (3) the turning point at which erosion becomes a deliberate autocratic project, analyzing the “qualitative leap” that transforms institutional decay into a strategy of power capture; and (4) resistance strategies, where an “architecture of democratic resilience” based on proactive civic vigilance is proposed. It is concluded that erosion arises from interrelated factors, from legacies of exclusion to current dynamics of polarization, and that autocratization represents a contingent risk, not an inevitable one, to the extent that institutional responses and citizen mobilization are effective. Thus, the article systematizes contemporary threats to democracy and articulates a model of active resilience for its sustainability.
Keywords: Democratic erosión; autocratization; institutional resilience; political polarization